An Overview of Remdesivir and Aspirin Treatment in COVID-19 - Haq, Syed Manzoor ul; Hassan, Neelma (Darul Yasin Al Sys, 2023)
The SARS-CoV-2 causes disease COVID-19, which is being spread worldwide with critical illnesses, respiratory syndrome and thromboembolism. To overcome this pandemic hassle in urgent, use “specific conventional drug” because there is no specific authorized antiviral drugs for COVID-19. The Gilead Science identified that Remdesivir most favorable treatment for COVID, as reduced fatality in people. Remdesivir is a trial agent with broad spectrum antiviral drug against SARS-CoV and MERS, potently inhibition of RdRp is identified as mode of action. However, there is urgent need to improve the efficacy and safety of these diagnostic investigations. The initial use of aspirin in COVID-19 patients is expected to reduce the incidence complications, shorten period of hospital duration and reduce the incidence of cardiovascular problems and its effects are recognized to inhibit COX, PGE2 in macrophages, fusion AcCoA to E1A-associated protein p300 and NF-kB factors pathway.